Introducing the Oral‐B iO electric toothbrush: next generation oscillating‐rotating technology. (3rd April 2020) - Adam, Ralf
Abstract : Purpose: A novel oscillating‐rotating electric toothbrush (Oral‐B iO) has been developed with a linear magnetic drive, resulting in oscillation‐rotations with micro‐vibrations. The mechanism directs motor energy directly to the bristle tips. The brush also has a redesigned round brush head and smart pressure sensor to enhance plaque removal and encourage proper brushing technique. Methods: The plaque removal and gingival health effects of this new electric toothbrush technology were evaluated in three randomized controlled studies summarized in this supplement, including an 8‐week trial versus a manual toothbrush, an 8‐week trial versus a premium sonic toothbrush, and a single‐brushing, repetitive‐use study versus a manual toothbrush. Results: Outcomes from these studies demonstrate statistically significantly greater plaque removal and gingival health improvements for the Oral‐B iO toothbrush technology versus manual and sonic toothbrush controls. Plaque removal advantages demonstrated in the replicate‐use single‐brushing trial resulted in significant gingival health benefits as evidenced in the longer‐term trials. In addition, gingivitis case status assessments based on the American Academy of Periodontology (AAP) and European Federation of Periodontology (EFP) guidelines show that over 80% of subjects using the Oral‐B iO transitioned from 'gingivitis' (≥10% bleeding sites) at baseline to 'generally healthy' (<10% bleeding sites) at week 8 in both longer‐term clinical trials, versus 24% in the manual toothbrush group and 53% in the sonic toothbrush group. Conclusions: This uniquely designed oscillating‐rotating electric toothbrush with a linear magnetic drive delivers significantly greater plaque removal and gingival health benefits with additional features to improve brushing experience and clinical outcomes.